Internações por condições sensíveis à atenção primária como indicador de desempenho da rede de cuidados de saúde - Deininger, Layza de Souza Chaves (2015)
Sensitive Conditions Primary health problems are treated by typical actions of the first level of health care, so that in situations of absence of effective service requires the use of specialized services in hospitals. Thus, hospitalizations are used as indicators to assess and monitor the effectiveness of Primary Health Care. The study is justified by the need to advance the discussion on health indicators to support managers in the decision-making process with regard to the proper planning of health actions that are often distorted and generate financial losses due to failure in planning, so that meet the needs of users of health services, primarily in the area of primary care while ordinate of health care. It is an exploratory, descriptive, ecological and inferential with quantitative and qualitative approaches. Quantitative results were analyzed based on the hypothesis tests for equal proportions and trends in proportions. Qualitative analysis was performed based on discourse analysis technique to shed proposed by José Luiz Fiorin. There was a downward trend in hospitalizations caused by primary care-sensitive conditions. in the city of João Pessoa/PB, from 2008 to 2013. However, there was an average of 16% of hospital expenses with preventable diseases. Analysis of the 19 groups of hospitalizations sensitive conditions. revealed that three groups (16%) did not show any trend and seven groups (37%) had growing trend of admissions. It was also observed that there are weaknesses in the planning process managers; failures in the network of health care and professional work process. It is suggested continuous investment in primary care in order to strengthen services so that health actions are carried out in an efficient and timely manner, aiming to avoid Sensitive Conditions Hospitalization for primary care; reduction in financial costs and unnecessary access to the services offered by the municipal health.